2004
DOI: 10.1103/physrevlett.92.156102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forces Caused by the Confinement of Thermal Noise

Abstract: We have investigated spontaneous surface instabilities of very thin polymer films. Film stability and the wavelength of the dominating unstable mode were found to depend sensitively on the media adjacent to the film. Our experimental results cannot be explained by van der Waals interactions alone. To account for the presence of an additional destabilizing force, we propose that the geometrical confinement of thermally excited acoustic waves gives rise to a force that is strong enough to destabilize thin films.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…As opposed to embossing methods, this lithographic mode minimizes the contact area of the template and the resist, significantly facilitating the template release. While a number of film destabilization mechanisms were recently reported, [7][8][9][10][11][12][13][14] the amplification of surface waves by an electric field is the most popular implementation. Electrohydrodynamic (EHD) lithography involves the use of a polymer-air bilayer in a capacitor device.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to embossing methods, this lithographic mode minimizes the contact area of the template and the resist, significantly facilitating the template release. While a number of film destabilization mechanisms were recently reported, [7][8][9][10][11][12][13][14] the amplification of surface waves by an electric field is the most popular implementation. Electrohydrodynamic (EHD) lithography involves the use of a polymer-air bilayer in a capacitor device.…”
Section: Introductionmentioning
confidence: 99%
“…However, alternative origins of G(h 0 ) have also been proposed [15,[20][21][22][23]. By assuming the non-retarded vdW potential for G(h 0 ), namely Gðh 0 Þ ¼ ÀA=12ph 2 0 where A is the Hamaker constant, and substituting it in Eqs.…”
Section: Theorymentioning
confidence: 99%
“…In Fig. 2 is plotted G 0 0 (h 0 ) for air-PS-SiO x -Si assuming several origins proposed of G(h 0 ), including the non-retarded vdW interactions [6], full vdW interactions [15] and the confined phonon fluctuation field [20,21]. As seen, for all these origins assumed of G(h 0 ), the spinodal G 00 (h 0 ) = 0 occurs at h 0 P 160 nm, showing the h 0 = 3 nm film chosen for this study to lie well inside the spinodal region on theoretical grounds.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most studies in this field have focused on the forces mentioned above and assumed that other possible instability-driving forces are negligible. New experimental and theoretical investigations have indicated that charged surfactants [13], external electric field [14][15][16][17][18], surface elasticity, and thermal field [19][20][21][22][23][24] may play a vital role in these surface phenomena. Among these, external electric field has been proposed for use in electrostatic lithography and surface pattern development due to the high sensitivity of thin liquid films to electrostatic forces [15,16].…”
Section: Introductionmentioning
confidence: 99%